Cooling tube for liquid-cooled charging cable and method for producing same

CN122878738APending Publication Date: 2026-10-09SICHUAN JIUZHOU WIRE & CABLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611043973.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0008]本发明是为了解决现有的液冷充电电缆用冷却无法兼具长期耐高温、耐水解、高散热性能和高柔韧性的技术问题,目的在于提供一种液冷充电电缆用冷却管及其制备方法,通过结构设计、填料改性和管材配方设计,实现了冷却管高散热、耐高温、耐水解、高柔韧的综合性能,适配大功率液冷充电电缆的使用需求,同时配合工艺创新提升管材成型精度与稳定性

Benefits of technology

[0056]1. 本发明通过采用改性复合填料提高了管材的耐水解性能和长期换热稳定性,提升填料与有机高分子的界面结合力,使管材弯折韧性提高,避免了产生裂纹,同时在冷却管配方中加入烷氧基封端有机硅,镶嵌聚氨酯分子链间隙,形成贯穿材料的疏水网络,同时平衡刚性填料与柔性聚氨酯的相容性,搭配水解稳定性,使最终的冷却管的综合性能得到提高:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878738A_ABST
    Figure CN122878738A_ABST
Patent Text Reader

Abstract

The application discloses a cooling pipe for a liquid-cooled charging cable and a preparation method thereof, and relates to the technical field of high polymer materials.The inner wall of the pipe body of the cooling pipe is provided with a plurality of T-shaped cavities which extend spirally along the axial direction of the cooling pipe.The raw materials include the following components in the proportions: 52-58 parts of polyether polyurethane elastomer, 18-26 parts of ethylene-octene copolymer, 6-9 parts of ethylene-vinyl acetate copolymer and acrylate elastomer compound, 22-28 parts of modified composite filler, 5-7 parts of mixed oil, 1.2-1.8 parts of compatibility agent, 1.2-1.8 parts of alkoxyl-terminated organosilicon and 0.3-0.6 parts of hydrolysis-resistant stabilizer.The modified composite filler is composed of inorganic filler powder, organosilicon hydrophobic film and flexible polyester transition layer from the inside to the outside.The application realizes the comprehensive performance of high heat dissipation, high temperature resistance, hydrolysis resistance and high flexibility of the cooling pipe through structural design, filler modification and pipe material formula design, and meets the use requirements of the high-power liquid-cooled charging cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a cooling pipe for liquid-cooled charging cables and its preparation method. Background Technology

[0002] With the rapid development of the new energy vehicle industry, high-power fast charging has become the mainstream development direction of the industry. High-current charging will cause a lot of Joule heat to be generated in the charging cable. If the heat cannot be dissipated in time, it will cause cable aging, insulation failure, and even safety accidents. Therefore, liquid-cooled charging cables have become the core supporting products of high-power charging equipment, and the cooling pipe is the key component inside the liquid-cooled cable that carries the coolant and realizes heat exchange.

[0003] Currently, the cooling pipes used in liquid-cooled charging cables on the market are mainly divided into two categories, both of which have obvious defects:

[0004] One type is a metal cooling tube: metal has excellent thermal conductivity, but the material is hard and has extremely poor flexibility. During use, the charging cable needs to be repeatedly bent and dragged. The metal cooling tube is prone to fatigue fracture due to long-term bending stress. At the same time, the heavy weight of the metal tube will increase the load on the charging gun and cable, affecting the user experience.

[0005] Another type is polyurethane cooling pipes: Traditional polyurethane pipes are flexible and easy to process, but the basic polyurethane formulation lacks high-temperature resistance, and the long-term operating temperature is generally below 80℃. Meanwhile, the coolant in a liquid cooling system is constantly at a high temperature, and since coolants are often water-based, ordinary polyurethane has weak hydrolysis resistance. After long-term immersion, problems such as pipe wall bulging, cracking, and significant degradation of mechanical properties can occur, severely shortening the cable's lifespan. Furthermore, some modified polyurethane formulations focus on gloss and general mechanical properties, lacking specialized formulations for long-term high-temperature (105℃) and high-coolant-temperature operating conditions.

[0006] In addition, the inner walls of existing cooling pipes are all smooth, and when the coolant flows, it is easy to form a stable laminar flow close to the pipe wall. The effective heat exchange area between the coolant and the pipe wall is small and the flow pattern is simple, making it difficult to meet the heat dissipation requirements of ultra-high power charging.

[0007] In summary, existing liquid-cooled charging cables cannot simultaneously achieve long-term high-temperature resistance, hydrolysis resistance, high heat dissipation performance, and high flexibility. Therefore, this invention is proposed. Summary of the Invention

[0008] This invention aims to address the technical problem that existing liquid-cooled charging cables cannot simultaneously achieve long-term high-temperature resistance, hydrolysis resistance, high heat dissipation performance, and high flexibility. The purpose is to provide a cooling pipe for liquid-cooled charging cables and its preparation method. Through structural design, filler modification, and pipe formulation design, the cooling pipe achieves comprehensive performance of high heat dissipation, high-temperature resistance, hydrolysis resistance, and high flexibility, meeting the application requirements of high-power liquid-cooled charging cables. At the same time, process innovation improves the forming accuracy and stability of the pipe.

[0009] The present invention is achieved through the following technical solution.

[0010] The first objective of this invention is to provide a cooling tube for a liquid-cooled charging cable, wherein the inner wall of the cooling tube is integrally formed with a plurality of T-shaped cavities, and the T-shaped cavities extend spirally along the axial direction of the cooling tube.

[0011] The cooling pipe comprises the following raw materials in parts by weight:

[0012] 52-58 parts of polyether-type polyurethane elastomer, 18-26 parts of ethylene-octene copolymer, 6-9 parts of ethylene-vinyl acetate copolymer and acrylate elastomer blend, 22-28 parts of modified composite filler, 5-7 parts of mixed oil, 1.2-1.8 parts of (styrene-maleic anhydride copolymer) compatibilizer, 1.2-1.8 parts of alkoxy-terminated organosilicon, and 0.3-0.6 parts of (carbodiimide) hydrolysis-resistant stabilizer;

[0013] The modified composite filler has a core-shell structure, with an inner inorganic filler powder, an intermediate organic silicon hydrophobic film, and an outer flexible polyester transition layer.

[0014] Regarding the structural innovation of the cooling pipe in this invention:

[0015] Existing liquid-cooled pipes rely solely on a single protrusion on the outer or inner wall to increase the heat exchange area, resulting in weak fluid spiral disturbance and low heat dissipation efficiency. To address this, this invention incorporates a T-shaped cavity extending spirally along the cooling pipe's axial direction within the pipe wall. Unlike external ribs and single-tooth protrusions on the inner wall, this invention's T-shaped cavity features a double-layered heat exchange wall. As the coolant flows through, vortex turbulence is generated, disrupting the laminar boundary layer of the pipe wall. The spiral axial extension structure continuously disturbs the fluid throughout the entire process, significantly improving the heat exchange contact area and efficiency. Furthermore, the integral co-extrusion molding eliminates adhesive gaps, eliminating leakage risks under high-pressure coolant conditions and making it suitable for high-power, fast-charging, high-flow-rate coolant circulation systems.

[0016] Innovations of the modified composite filler in this invention:

[0017] The modified composite filler of the present invention has a core-shell structure, with an inorganic filler powder inside, a silane hydrophobic layer in the middle, and a flexible polyester transition layer on the outside. The silane hydrophobic layer forms an organic silicon hydrophobic film on the surface of the filler, providing a long-lasting hydrophobic barrier and blocking the water molecule penetration channel. The flexible transition chain is then grafted onto the outer layer of silane to reduce the modulus difference between the inorganic filler and the polyurethane matrix, eliminate micro-gaps at the interface, improve the bending toughness of the pipe, and prevent filler agglomeration from causing micro-cracks in the pipe wall. The modified composite filler of this invention has the following characteristics: 1. The powder surface is completely hydrophobic, significantly reducing water absorption and microscopically blocking moisture from penetrating the polyurethane molecular chains, thus effectively improving the high-temperature hydrolysis resistance at 105℃; 2. The inorganic filler and organic polymer are bonded by covalent bonds, doubling the interfacial bonding force, preventing filler precipitation, material delamination, and pipe wall whitening during long-term high-temperature use; 3. The filler is uniformly dispersed at the nanoscale within the polyurethane system, without agglomeration points, significantly reducing the pipe's thermal deformation coefficient, and the spiral T-shaped cavity is not easily deformed at high temperatures, ensuring long-term stable heat exchange structure. Therefore, the modified composite filler of this invention effectively improves the pipe's hydrolysis resistance and long-term heat exchange stability, and the strong interfacial bonding force between the filler and organic polymer improves the pipe's bending toughness, preventing cracking.

[0018] Regarding the innovative formulation of the cooling pipe of this invention:

[0019] This invention incorporates alkoxy-terminated organosilicon into the material system through a dual approach of filler grafting and matrix blending, combined with a long-lasting hydrolytic stabilizer and a high-temperature compatible compound system. The organosilicon segments are uniformly embedded in the gaps between polyurethane molecular chains, forming a hydrophobic network that runs through the material. At the same time, it balances the compatibility between rigid fillers and flexible polyurethane, and is simultaneously resistant to water-based ethylene glycol coolant and oil-based insulating coolant, thus solving the industry contradiction of poor oil resistance of single polyether TPU and insufficient strength of pure organosilicon pipes.

[0020] The innovation of this invention lies in the dual-introduction formulation system of alkoxy-terminated organosilicon filler grafting and matrix blending, which is compounded with a long-lasting hydrolysis-resistant stabilizer of carbodiimide, a high-temperature compatible compound system of styrene-maleic anhydride, a composite modified resin of ethylene-octene / acrylate elastomer, a high-temperature resistant multi-element mixed lubricating grease and a double-layer core-shell structure modified inorganic filler. The components complement each other and form a multi-level synergistic effect.

[0021] Each component has a clear function and targets the inherent defects of a single raw material: polyether-type polyurethane elastomer provides basic hydrolysis and bending resistance as a flexible matrix, but its oil swelling resistance is poor when used alone; alkoxy-terminated organosilicon has both hydrophobic and oil-resistant properties, and is dispersed through a dual-pathway dispersion of filler covalent grafting and matrix melt blending, simultaneously constructing a continuous hydrophobic network on the filler surface and inside the resin; carbodiimide stabilizer can capture polyurethane hydrolysis chain breaks, forming a dual protection of "physical barrier penetration + chemical termination of hydrolysis" with organosilicon; styrene-maleic anhydride compatibilizer acts as an interfacial bridging medium, eliminating the high-temperature phase separation defects of polyurethane, organosilicon, and polyolefin multiphase systems; the ethylene-octene and acrylate elastomer composite system improves melt flowability and oil resistance; the modified composite filler relies on the synergistic reinforcement of silica, mica powder, talc powder, and nano titanium dioxide to offset the material strength reduction problem caused by organosilicon; the high flash point synthetic naphthenic oil composite lubrication system avoids grease migration and precipitation under long-term working conditions at 105℃.

[0022] The system exhibits multiple key synergistic effects: First, the synergistic effect of alkoxylated organosilicon and carbodiimide hydrolysis protection: organosilicon blocks the penetration of water and oil media into the material, while carbodiimide blocks the hydrolysis chain reaction of polyurethane, resulting in a significant extension of service life in humid and hot environments. Second, the synergistic effect of grafted modified filler and matrix dispersed organosilicon with global hydrophobicity: the surface of micro-filler particles and the macro-resin matrix simultaneously form a hydrophobic barrier, significantly increasing the resistance to media penetration. Third, the synergistic effect of rigid modified filler and flexible polyurethane-organosilicon matrix with mechanical balance: it balances the toughness of the pipe under repeated bending and the pressure resistance of the coolant, solving the defects of pure organosilicon pipes such as easy deformation and insufficient pressure resistance. Fourth, the synergistic effect of styrene-maleic anhydride compatibilizer and organosilicon interface compatibility: it avoids the aggregation and precipitation of siloxane chains, maintaining the uniform structure of the material for a long time. Fifth, the synergistic effect of acrylate elastomer, organosilicon, and high-temperature resistant lubricating oil with oil resistance: it significantly reduces the volume swelling rate after immersion in oil-based coolant.

[0023] Based on the unique combination of components and multiple synergistic mechanisms of this formula, the material achieves several key performance breakthroughs: it can be used with both water-based ethylene glycol and oil-based silicone oil coolants, solving the industry contradiction of poor oil resistance of single polyether TPU and insufficient mechanical strength of pure organosilicon pipes; it exhibits no delamination, no oil separation, and minimal dimensional deformation at long-term high temperature of 105℃.

[0024] Preferably, the weight ratio of the ethylene-vinyl acetate copolymer to the acrylate elastomer compound is (5-8):1.

[0025] Preferably, the composite filler in the modified composite filler includes silica, mica powder, ultrafine talc powder, and nano titanium dioxide, with a weight ratio of (10-14):3:(18-23):(0.8-1.5).

[0026] Preferably, the blended oil is composed of synthetic naphthenic oil, vinyl silicone oil, and refined palm oil in a weight ratio of (4.5-5.5):1:(2.2-2.8).

[0027] Preferably, the alkoxy-terminated organosilicon is either dimethoxylated polydimethylsiloxane or monomethoxylated monomethyl polydimethylsiloxane. Both are reactive organosilicones, unlike ordinary inert methyl silicone oil. Their molecules carry hydrolyzable methoxy reactive groups, which can be permanently grafted onto the surface of the modified filler through covalent bonds, and simultaneously interpenetrate between polyurethane molecular chains during melt blending. Among them, dimethoxylated polydimethylsiloxane has alkoxy crosslinking sites at both ends of the molecule, which can form a continuous silicon-oxygen hydrophobic network that penetrates the material, and has the best hydrolysis resistance and oil resistance, making it the preferred raw material of this invention. Monomethoxylated monomethyl polydimethylsiloxane has reactive alkoxy groups on only one side, resulting in better melt flowability and suitability for cooling pipe extrusion processing.

[0028] Preferably, the modified composite filler is prepared by:

[0029] The composite filler was added to a hydrogen peroxide solution, ultrasonically dispersed at 40-50℃, and dried to obtain the activated filler.

[0030] The activated filler was added to N,N-dimethylformamide, followed by the addition of alkoxy-terminated organosilicon and reaction for 1-2 hours. Then, dibutyl dilauric acid (catalyst) and polyester polyol solution were added. After the reaction was completed, the mixture was filtered to obtain the modified composite filler.

[0031] Because conventional inorganic powders such as silica, mica powder, ultrafine talc powder, and nano-titanium dioxide have a large number of polar hydroxyl groups on their surfaces, they have three fatal defects: 1. The powders readily adsorb free water from the air. When mixed into a polyurethane matrix, water molecules will continuously damage the polyurethane urethane bonds under high-temperature conditions, accelerating hydrolysis and aging; 2. The polarity difference between the inorganic powders and organic polyurethane and polyolefin polymer interfaces is huge. Direct blending easily leads to agglomeration, causing stress concentration inside the pipe and making it prone to cracking after bending; 3. The powder surface lacks a hydrophobic functional layer, allowing coolant moisture to penetrate into the material along the filler-matrix interface, resulting in a precipitous decline in mechanical properties over long-term use. Without the activation and step grafting modification specific to this invention, simply physically mixing the fillers will result in a significant decrease in the pipe's high-temperature resistance, hydrolysis resistance, dimensional stability, and bending life, failing to meet the harsh operating conditions of liquid-cooled cables under long-term high-temperature conditions of 105°C and immersion in water-containing coolant.

[0032] Based on this, the composite filler has been modified in this invention. The innovative aspect of this invention lies in:

[0033] First, the composite filler is treated with a low-temperature hydrogen peroxide ultrasonic activation system at 40~50℃. Under the dual effects of gentle heating at 40~50℃ and ultrasonic cavitation, a small amount of hydroxyl radicals are slowly released. This only etches the shallow lattice on the surface of the powder, without damaging the self-reinforcing framework of the silica, talc, and mica powder. The free radicals can remove oil and dust impurities from the powder surface, and at the same time, the number of active hydroxyl groups on the powder surface can be controlled to increase (moderate activation to avoid excessive hydroxyl groups from aggravating hydrophilicity), providing sufficient reaction sites for the subsequent isocyanate silane grafting reaction.

[0034] Then, isocyanate alkoxy-terminated organosilicon is added and covalently bonded to the activated hydroxyl groups on the powder surface. The isocyanate alkoxy-terminated organosilicon has both silane coupling and crosslinking functions and organosilicon hydrophobicity. Unlike ordinary aminosilanes, the alkoxy end can penetrate into the polyurethane matrix and is compatible. The silicon-oxygen backbone provides a long-lasting hydrophobic barrier to block the water molecule penetration channel, thereby constructing an organosilicon hydrophobic film on the filler surface.

[0035] Finally, polyester polyol is slowly added dropwise. The dibutyl dilauric acid catalyst catalyzes the secondary grafting of polyester hydroxyl groups and silane residual active groups, and then flexible polyester segments are grafted onto the outer layer of organosilicon. This reduces the modulus difference between inorganic fillers and polyurethane matrix, eliminates interfacial micro-gaps, improves the bending toughness of the pipe, and avoids filler agglomeration that causes micro-cracks in the pipe wall.

[0036] Therefore, this invention achieves covalent hydrophobic coating of inorganic fillers by performing low-temperature hydrogen peroxide ultrasonic activation and step grafting modification on composite fillers, ultimately forming a double-layer core-shell modified structure of inorganic powder-silane hydrophobic layer-flexible polyester transition layer, solving the inherent defects of powder water absorption and interface separation, thereby improving the comprehensive performance of finished pipes.

[0037] Preferably, the weight ratio of the composite filler, alkoxy-terminated organosilicon, polyester polyol solution, and dibutyl dilauric acid is 10:(0.9-1.1):(16-19):0.01.

[0038] Preferably, the raw material of the cooling pipe also contains 0.2-0.4 parts by weight of a light stabilizer, wherein the light stabilizer is at least one of benzophenone or benzotriazole light stabilizers.

[0039] Preferably, the height of a single T-shaped cavity is 0.8-2.5 mm, and the helix angle of the spiral pattern formed by the T-shaped cavity is 15°-45°.

[0040] A second objective of this invention is to provide a method for manufacturing a cooling tube for a liquid-cooled charging cable, comprising the following steps:

[0041] (1) Preparation of modified composite fillers

[0042] After drying the composite filler, it was added to a hydrogen peroxide solution, heated to 40-50℃, ultrasonically dispersed, filtered, and dried to obtain the activated filler.

[0043] The activated filler was added to N,N-dimethylformamide, and the temperature was gradually increased to 80℃ and held. Alkoxy-terminated organosilicon was added and reacted for 1-2 hours. Then, dibutyl dilauric acid catalyst was added, and polyester polyol solution was added dropwise. After the addition was completed, the reaction was held at the temperature for 2.5-3.5 hours. After the reaction, the filler was filtered, washed, and desolventized to obtain the modified composite filler.

[0044] (2) Preparation of polyurethane granules

[0045] A three-stage compound mixing process is adopted, in which the materials are first premixed at low speed according to the formula, then mixed at high speed, and finally mixed in a closed environment.

[0046] After the material is internally mixed, it is melt-blended through a twin-screw extruder, extruded, and pelletized to obtain polyurethane granules;

[0047] (3) Cooling pipe extrusion molding

[0048] Polyurethane granules are fed into a single-screw extruder, and the material is extruded through a mandrel to form a tube blank with a spiral T-shaped cavity on the inner wall. After cooling, the tube blank is subjected to low-temperature tempering to eliminate extrusion internal stress and obtain the finished product.

[0049] The preparation method of this invention further improves and ensures the comprehensive performance of the finished product through the synergistic effects of double-layer core-shell stepped filler modification, three-stage mixing, and gradient stress elimination extrusion: First, the basic performance of the filler is improved by modifying the double-layer core-shell stepped filler, which strengthens the temperature resistance and hydrolysis resistance of the pipe at the microscopic level. Then, through three-stage gradient shear mixing of low-speed premixing, high-speed mixing, and closed mixing, the interfacial stress of the multiphase polymer is gradually released, avoiding the breakage of polyurethane molecular chains caused by high-temperature single strong shear. Then, through melt buffering and heat preservation, three-stage gradient water cooling, 60-70℃ low-temperature tempering stress elimination, and core mold traction linkage speed regulation, the internal stress of extrusion is completely eliminated, solving the mass production problems of high-temperature deformation, eccentricity, and uneven tooth shape of spiral cavity pipes, and finally ensuring the molding accuracy and performance stability of the product.

[0050] Preferably, the specific steps of the three-stage compound mixing process include:

[0051] First, put the polyether-type polyurethane elastomer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer and acrylate elastomer compound into a low-speed mixer and mix for 5-8 minutes to obtain a premixed material.

[0052] Add modified composite filler, mixed oil, compatibilizer, alkoxy-terminated organosilicon, and hydrolysis-resistant stabilizer to the premixed material, and then mix in a high-speed mixer for 8-12 minutes.

[0053] Finally, the high-speed mixed material is sent to a closed mixer for refining for 10-15 minutes.

[0054] Preferably, the single-screw extruder is provided with a melt insulation buffer section at the rear end of the die head, and the cooling adopts a three-stage gradient water cooling: the first stage water temperature is 45-55℃, the second stage water temperature is 30-40℃, and the third stage water temperature is 20-28℃.

[0055] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0056] 1. This invention improves the hydrolysis resistance and long-term heat exchange stability of the pipe by using modified composite fillers, enhances the interfacial bonding force between the filler and organic polymers, improves the bending toughness of the pipe, and avoids cracking. Simultaneously, alkoxy-terminated organosilicon is added to the cooling pipe formulation, embedding it into the gaps between polyurethane molecular chains to form a hydrophobic network that penetrates the material. This balances the compatibility between the rigid filler and the flexible polyurethane, and addresses hydrolysis stability, ultimately improving the overall performance of the cooling pipe.

[0057] Improved heat resistance: Stable at 105℃ for long-term continuous use, and no softening or deformation at short-term peak temperature of 120℃, breaking through the traditional TPU's long-term use limit of 80℃;

[0058] Media resistance: It can withstand both ethylene glycol aqueous solution and silicone oil coolant. After immersion in water for 500 hours, the strength decreases by less than 7%, while the strength of ordinary TPU decreases by more than 40% after alternating immersion in water and oil.

[0059] Improved hydrolysis resistance: Strength retention rate is greater than 90% after hydrolysis at 85℃ for 168 hours.

[0060] Processing stability: The synthetic naphthenic oil composite lubrication system does not separate oil for a long time at 105℃, and will not contaminate the copper conductor and insulation layer of the cable;

[0061] Bending resistance and toughness: No cracks after 10,000 repeated bends, suitable for charging guns that are frequently dragged and bent.

[0062] 2. This invention, by setting a T-shaped cavity that spirally extends along the cooling pipe axis inside the pipe wall, and continuously agitating the coolant within the spiral T-shaped double-walled heat exchange cavity, eliminates stagnant laminar flow on the pipe wall. Under the same coolant flow rate and temperature rise conditions, the heat exchange efficiency is increased by 31%-33% compared to traditional smooth inner wall cooling pipes. Under the same heat dissipation requirements, the diameter of the cooling pipe can be reduced, simplifying the overall outer diameter of high-power liquid-cooled cables, reducing the overall weight of the charging gun, and improving the comfort of handheld operation.

[0063] 3. This invention improves the uniformity of component dispersion by 48% through three-stage mixing, resulting in a radial eccentricity of the pipe ≤0.3mm; three-stage gradient water cooling and low-temperature tempering eliminate extrusion internal stress, achieving a dimensional deformation rate ≤0.8% after 24 hours at 105℃; and mandrel traction linkage speed regulation ensures uniform pitch and cross-sectional dimensions of the spiral T-shaped cavity throughout the pipe. Through synergistic process improvements, the pipe forming accuracy and stability are enhanced.

[0064] 4. The cooling pipe of the present invention has no risk of metal fatigue fracture, excellent flexibility, and is suitable for high-power fast-charging liquid-cooled charging equipment; the material does not require additional surface polishing or coating treatment, and is extruded in one piece, simplifying the cable processing process; the material has excellent weather resistance, and the mechanical decay of outdoor charging piles is slow under long-term sun exposure and ultraviolet environment, extending the service life of the entire charging equipment by more than 2 times. Attached Figure Description

[0065] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be considered as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort. In the drawings:

[0066] Figure 1 This is a schematic cross-sectional view of the cooling pipe of the present invention. Detailed Implementation

[0067] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the illustrative embodiments and descriptions of the present invention are only used to explain the present invention and are not intended to limit the present invention.

[0068] The embodiments of the present invention will be described in detail below. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.

[0069] The "scope" disclosed in this invention is defined in the form of a lower limit and an upper limit. A given scope is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific scope. The scope defined in this way can include or exclude end values, and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a scope.

[0070] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.

[0071] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.

[0072] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other substances not listed may also be included, or that only the listed substances may be included.

[0073] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0074] In order to solve the technical problem that existing liquid-cooled charging cables cannot simultaneously possess long-term high temperature resistance, hydrolysis resistance, high heat dissipation performance and high flexibility, this invention proposes a cooling pipe for liquid-cooled charging cables.

[0075] The cooling pipe has a structure in which several T-shaped cavities are integrally formed on the inner wall of the pipe, and the T-shaped cavities extend spirally along the axial direction of the cooling pipe; the number of T-shaped cavities is 6-26, and the height of a single T-shaped cavity is 0.8-2.5 mm; the spiral angle formed by the T-shaped cavities is 15°-45°.

[0076] The cooling pipe comprises the following raw materials in parts by weight:

[0077] The composition includes 52-58 parts of polyether-type polyurethane elastomer, 18-26 parts of ethylene-octene copolymer, 6-9 parts of ethylene-vinyl acetate copolymer and acrylate elastomer blend, 22-28 parts of modified composite filler, 5-7 parts of mixed oil, 1.2-1.8 parts of (styrene-maleic anhydride copolymer) compatibilizer, 1.2-1.8 parts of alkoxy-terminated organosilicon (such as isocyanate alkoxy-terminated organosilicon), and 0.3-0.6 parts of (carbodiimide) hydrolysis-resistant stabilizer; wherein the modified composite filler has a core-shell structure, with an inner inorganic filler powder, an intermediate organosilicon hydrophobic film, and an outer flexible polyester transition layer.

[0078] The method for preparing the cooling pipe includes the following steps:

[0079] (1) Preparation of modified composite fillers

[0080] First, silica, mica powder, ultrafine talc powder, and nano titanium dioxide are mixed in a certain proportion to obtain a basic composite filler. The filler is then placed in a vacuum oven and pre-dried at 80-90℃ for 2-3 hours. The dried basic composite filler is then placed in a hydrogen peroxide solution, heated to 42-48℃, ultrasonically dispersed for 12-18 minutes, filtered, and pre-dried with hot air. It is then transferred to a vacuum oven for deep drying at 70-80℃ to obtain the activated filler.

[0081] Under a nitrogen protective atmosphere, the activated filler was added to N,N-dimethylformamide, and a stepped heating method was adopted: first, the temperature was raised to 75℃ and held for 0.5 h, then raised to 80℃ and held, and isocyanate alkoxy-terminated organosilicon was added and stirred for 1.2-1.8 h; then, dibutyl dilauric acid catalyst was added, and polyester polyol solution (prepared by mixing polyester polyol and N,N-dimethylformamide at a weight ratio of 1:5) was added dropwise at a uniform rate, with the dropwise addition time controlled at 40-60 min. After the dropwise addition was completed, the reaction was continued at the temperature for 2.5-3.5 h; after the reaction was completed, the mixture was filtered while hot, and the filter residue was washed with N,N-dimethylformamide, and then subjected to vacuum desolventizing treatment to obtain the modified composite filler.

[0082] The purpose of the segmented step heating is to allow isocyanate alkoxy-terminated organosilicon molecules to slowly diffuse and uniformly adsorb onto the surface of the activated hydroxyl groups of the filler during the 75℃ low-temperature pre-heating stage, thus avoiding local self-polymerization and uneven grafting of silane caused by a single high temperature. Then, the temperature is raised to 80℃ for constant temperature reaction.

[0083] The purpose of the nitrogen protective atmosphere is to isolate water vapor and oxygen in the air, prevent isocyanate alkoxy-terminated organosilicon from failing when exposed to water and from high-temperature oxidation side reactions, and ensure that the conversion rate of the covalent grafting reaction remains stable at over 92%.

[0084] (2) Preparation of polyurethane granules (using a three-stage composite mixing process)

[0085] Step 1: Low-speed premixing: Add the polyether-type polyurethane elastomer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer and acrylate elastomer compound to a low-speed mixer and mix at 150-250 r / min and 50-60℃ for 5-8 min.

[0086] The second step is high-speed mixing: Modified composite filler, mixed oil, styrene-maleic anhydride copolymer compatibilizer, alkoxy-terminated organosilicon, and carbodiimide hydrolysis-resistant stabilizer are added to the premixed material in sequence, and then the mixture is transferred to a high-speed mixer and mixed at a speed of 600-800 r / min and a temperature of 60-80℃ for 8-12 min.

[0087] The third step is closed mixing: the material after high-speed mixing is fed into a closed mixer, the mixing temperature is 150-170℃ and the mixing time is 10-15min; after the mixing is completed, the material is fed into a twin-screw extruder, the temperature of each zone of the screw is controlled at 160-190℃, and after melt blending, it is extruded and pelletized to obtain polyurethane granules.

[0088] (3) Cooling pipe extrusion molding

[0089] Polyurethane granules are fed into a single-screw extruder, with the extruder body temperature controlled at 165-185℃ and the die head temperature at 170-180℃. A melt insulation buffer section is set at the rear of the die head, with the buffer section temperature maintained at 172-178℃. The extruder is equipped with a rotatable helical tooth mandrel, and the mandrel and traction machine adopt a linked speed regulation mode. The mandrel speed is 5-20 r / min, and the traction speed is synchronously matched with the mandrel speed (the speed matching ratio between the mandrel and the traction machine is 1:(1.2-2.0)).

[0090] The material is extruded through a mandrel to form a tube blank with a spiral T-shaped cavity on the inner wall. The tube blank is first vacuum sizing, and then enters a three-stage gradient water cooling zone for sequential cooling: the first stage water temperature is 45-55℃, the second stage water temperature is 30-40℃, and the third stage water temperature is 20-28℃. After cooling, it enters the online heat treatment zone and is held at 60-70℃ for 3-5 minutes for low-temperature tempering and shaping to eliminate extrusion internal stress. Finally, after online dimensional inspection and correction, traction, and winding, the finished cooling tube for liquid-cooled charging cables is obtained.

[0091] The technical solution of the present invention will be further described in detail below with reference to the embodiments.

[0092] It should be noted that, unless otherwise specified, the experimental methods used in the embodiments are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0093] Examples 1-3

[0094] The raw material weight ratio of a cooling pipe for a liquid-cooled charging cable is shown in Table 1.

[0095] Table 1. Raw material weight ratio for cooling pipes used in liquid-cooled charging cables in Examples 1-3

[0096] Polyether-type polyurethane elastomer 55 copies 52 copies 58 copies ethylene-octene copolymer 22 copies 26 copies 18 copies EVA + acrylate elastomer (7:1) 7 copies 6 copies 9 copies Modified composite filler (12:3:21:1) 25 copies 28 copies 22 copies New type of blended oil (5:1:2.5) 6 copies 7 copies 5 copies Styrene-maleic anhydride (SMA) compatibilizer 1.5 copies 1.8 copies 1.2 portions Dimethoxylated polydimethylsiloxane 1.5 copies 1.8 copies 1.2 portions Carbodiimide hydrolysis-resistant stabilizer 0.4 copies 0.6 copies 0.3 copies Light stabilizers (benzophenone derivatives) 0.3 copies 0.4 copies 0.2 copies

[0097] A method for manufacturing a cooling tube for a liquid-cooled charging cable includes the following steps:

[0098] I. Preparation of Modified Composite Fillers

[0099] (1) First, the silica, mica powder, ultrafine talc powder and nano titanium dioxide are mixed in proportion to obtain the basic composite filler, and then placed in a vacuum oven at 85°C for vacuum pre-drying for 2.5 hours.

[0100] (2) After drying, the composite filler is added to hydrogen peroxide solution, ultrasonically dispersed at 45°C for 15 min, filtered, dried with hot air, and then transferred to a vacuum oven at 75°C for deep drying to obtain activated composite filler.

[0101] (3) N,N-dimethylformamide was added under nitrogen protection and the temperature was increased in stages: first, the temperature was kept at 75℃ for 0.5h, then the temperature was increased to 80℃, and isocyanate alkoxy-terminated organosilicon was added and stirred for 1.5h.

[0102] (4) Add dibutyl dilauric acid catalyst, and add polyester polyol solution dropwise at a constant rate for 50 min. After the addition is completed, keep the temperature for 3 h.

[0103] (5) Filter while hot, rinse with N,N-dimethylformamide, and finally desolvent under vacuum to obtain the modified composite filler;

[0104] (6) Material ratio: Composite filler: Isocyanate alkoxy-terminated organosilicon: Polyester polyol solution: Dibutyl dilauric acid = 10:1:17.5:0.01.

[0105] II. Polyurethane Granule Preparation

[0106] (1) Low-speed premixing: The polyether-type polyurethane elastomer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer and acrylate elastomer compound were put into a low-speed mixer at a speed of 200 r / min and a temperature of 55℃ for 6 min;

[0107] (2) High-speed mixing: Add modified composite filler, mixed oil, styrene-maleic anhydride copolymer compatibilizer, dimethoxylated polydimethylsiloxane, carbodiimide hydrolysis stabilizer and benzophenone light stabilizer to the premixed material in sequence, transfer to a high-speed mixer, speed 700 r / min, temperature 70℃, mix for 10 min;

[0108] (3) Internal mixing: The material after high-speed mixing is fed into a closed internal mixer at a temperature of 160℃ and mixed for 12 minutes.

[0109] (4) Twin-screw extrusion: After the mixing is completed, the material is fed into the twin-screw extruder, and the temperature of each zone of the screw is controlled at 160-185℃. The material is then extruded and pelletized.

[0110] III. Cooling Pipe Extrusion Molding

[0111] (1) Feed polyurethane granules into a single screw extruder and control the extruder body at 170°C, the die head at 175°C, and the melt buffer section at 175°C.

[0112] (2) The core mold speed is 12 r / min, and the core mold and the traction machine are linked for speed regulation with a matching ratio of 1:1.6;

[0113] (3) The material is extruded through the mandrel to form a tube blank with a spiral T-shaped cavity on the inner wall. The tube blank is first vacuum sizing and then enters a three-stage gradient water cooling zone for sequential cooling: the first stage is 50°C, the second stage is 35°C, and the third stage is 25°C.

[0114] (4) After cooling, low-temperature tempering and shaping: heat preservation at 65℃ for 4 minutes; finally, online dimensional inspection, correction, traction, and winding are performed to obtain the finished product cooling pipe for liquid-cooled charging cables;

[0115] (5) Pipe structure: 16 T-shaped cavities on the inner wall, tooth height 1.6mm, helix angle 30°.

[0116] Comparative Example 1

[0117] The difference between this comparative example and Example 2 is that no composite filler modification is performed. Instead, the silica, mica powder, ultrafine talc powder, and nano titanium dioxide are directly mixed in the specified proportions and used. The rest of the operation methods remain unchanged.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 2 is that no activation treatment was performed during the modification of the composite filler, while the other operation methods remained unchanged.

[0120] Comparative Example 3

[0121] The difference between this comparative example and Example 2 is that the inner wall of the cooling pipe is smooth and no T-shaped cavity is provided, while the other operating methods remain the same.

[0122] Comparative Example 4

[0123] The difference between this comparative example and Example 2 is that the inner wall of the cooling pipe is provided with conventional protrusions, and the protrusions can be trapezoidal or square.

[0124] The above embodiments and comparative examples were subjected to performance tests. The test methods were as follows: media resistance test reference standard GB / T33594-2025 11.5.2, aging test reference standard GB / T 2951.12-2008, hydrolysis resistance test reference standard GB / T33594-2025 Appendix C, bending test reference standard GB / T 33594-2025 11.5.7.3, high temperature oil separation test reference standard GB / T 2951.12-2008, dimensional deformation test reference standard GB / T 2951.11-2008, and heat dissipation efficiency test reference standard CQC 1147-2025 Appendix F.

[0125] The results are shown in Table 2.

[0126] Table 2. Performance test results of the examples and comparative examples

[0127] Strength retention rate after 168 hours of resistance to medium at 120℃ 97% 97% 96% 65% 70% 73% 96% 96% Strength retention rate after aging at 105℃ for 240 hours 96% 97% 95% 65% 69% 71% 92% 93% Strength retention rate after hydrolysis at 85℃ for 168 hours 94% 95% 93% 58% 66% 68% 93% 92% 10,000 bending tests No cracks No cracks No cracks Microcracks appeared Cracks Cracks microcracks microcracks Oil separation at 105℃ (240h) No oil seepage No oil seepage No oil seepage Obvious oil seepage Oil seepage Oil seepage No oil seepage No oil seepage Dimensional deformation rate at 105℃ (24h) 0.7% 0.6% 0.8% 3.8% 3.4% 2.6% 1.0% 1.1% Relative heat dissipation efficiency (based on commercially available pure TPU tubing) +32% +33% +31% 100% +20% +22% +1% +5%

[0128] As can be seen from the data in Table 2:

[0129] A comparison of data from the embodiments of this invention and ordinary commercially available pure TPU smooth inner wall cooling pipes shows that the product of this invention has a much better retention rate of mechanical properties than ordinary pure TPU pipes under ethylene glycol aqueous solution and silicone oil coolant media environments, high temperature of 105℃ and high humidity hydrolysis test environment. It also has excellent bending performance, improved high temperature dimensional stability of the pipe, and combined with the spiral T-shaped structure, the heat dissipation efficiency is improved by more than 30%.

[0130] A comparison of the data from the embodiments of the present invention and the comparative examples shows that the processes of the comparative examples differ from those of the embodiments of the present invention, and the overall performance of their products is significantly reduced. This proves that only through the synergistic effect of the structural design, filler modification, and pipe formulation design of the present invention can the technical effect of improving the overall performance of the cooling pipe, including high heat dissipation, high temperature resistance, hydrolysis resistance, and high flexibility, be achieved.

[0131] Finally, it should be noted that the above specific embodiments are only used to describe the purpose, technical solution, and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation of the present invention and is not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the foregoing specific embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions or improvements can be made to some or all of the technical features. These modifications, equivalent substitutions, and improvements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A cooling pipe for a liquid-cooled charging cable, characterized in that, The inner wall of the cooling pipe is integrally formed with several T-shaped cavities, and the T-shaped cavities extend spirally along the axial direction of the cooling pipe. The cooling pipe comprises the following raw materials in parts by weight: 52-58 parts of polyether-type polyurethane elastomer, 18-26 parts of ethylene-octene copolymer, 6-9 parts of ethylene-vinyl acetate copolymer and acrylate elastomer blend, 22-28 parts of modified composite filler, 5-7 parts of mixed oil, 1.2-1.8 parts of compatibilizer, 1.2-1.8 parts of alkoxy-terminated organosilicon, and 0.3-0.6 parts of hydrolysis-resistant stabilizer; The modified composite filler has a core-shell structure, with an inner inorganic filler powder, a middle silane hydrophobic layer, and an outer flexible polyester transition layer.

2. The cooling pipe for a liquid-cooled charging cable according to claim 1, characterized in that, The weight ratio of the ethylene-vinyl acetate copolymer to the acrylate elastomer compound is (5-8):

1.

3. The cooling pipe for a liquid-cooled charging cable according to claim 1, characterized in that, The modified composite filler includes silica, mica powder, ultrafine talc powder, and nano titanium dioxide in a weight ratio of (10-14):3:(18-23):(0.8-1.5).

4. The cooling pipe for a liquid-cooled charging cable according to claim 1, characterized in that, The preparation method of the modified composite filler is as follows: The composite filler was added to a hydrogen peroxide solution, ultrasonically dispersed at 40-50℃, and dried to obtain the activated filler. The activated filler was added to N,N-dimethylformamide, followed by the addition of alkoxy-terminated organosilicon and reaction for 1-2 hours. Then, dibutyl dilauric acid and polyester polyol solution were added. After the reaction was completed, the mixture was filtered to obtain the modified composite filler.

5. A cooling pipe for a liquid-cooled charging cable according to claim 4, characterized in that, The weight ratio of composite filler, alkoxy-terminated organosilicon, polyester polyol solution, and dibutyl dilauric acid is 10:(0.9-1.1):(16-19):0.

01.

6. A cooling pipe for a liquid-cooled charging cable according to claim 1, characterized in that, The raw material of the cooling pipe also contains 0.2-0.4 parts by weight of light stabilizer, which is at least one of benzophenone and benzotriazole light stabilizers.

7. A cooling pipe for a liquid-cooled charging cable according to claim 1, characterized in that, The height of a single T-shaped cavity is 0.8-2.5 mm, and the helical pattern formed by the T-shaped cavity has an elevation angle of 15°-45°.

8. The method for preparing a cooling pipe for a liquid-cooled charging cable as described in claim 4, characterized in that, Includes the following steps: (1) Preparation of modified composite fillers After drying the composite filler, it was added to a hydrogen peroxide solution, heated to 40-50℃, ultrasonically dispersed, filtered, and dried to obtain the activated filler. The activated filler was added to N,N-dimethylformamide, and the temperature was gradually increased to 80℃ and held. Alkoxy-terminated organosilicon was added and reacted for 1-2 hours. Then dibutyl dilauric acid was added, followed by the dropwise addition of polyester polyol solution. After the dropwise addition was completed, the reaction was held at the temperature for 2.5-3.5 hours. After the reaction, the filler was filtered, washed, and desolventized to obtain the modified composite filler. (2) Preparation of polyurethane granules A three-stage compound mixing process is adopted, in which the materials are first premixed at low speed according to the formula, then mixed at high speed, and finally mixed in a closed environment. After the material is internally mixed, it is melt-blended through a twin-screw extruder, extruded, and pelletized to obtain polyurethane granules; (3) Cooling pipe extrusion molding Polyurethane granules are fed into a single-screw extruder, and the material is extruded through a mandrel to form a tube blank with a spiral T-shaped cavity on the inner wall. After cooling, the tube blank is subjected to low-temperature tempering to eliminate extrusion internal stress and obtain the finished product.

9. The method for preparing a cooling pipe for a liquid-cooled charging cable according to claim 8, characterized in that, The specific steps of the three-stage compound mixing process include: First, put the polyether-type polyurethane elastomer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer and acrylate elastomer compound into a low-speed mixer and mix for 5-8 minutes to obtain a premixed material. Add modified composite filler, mixed oil, compatibilizer, alkoxy-terminated organosilicon, and hydrolysis-resistant stabilizer to the premixed material, and then transfer it to a high-speed mixer to mix for 8-12 minutes. Finally, the high-speed mixed material is fed into a closed mixer and mixed for 10-15 minutes.

10. A method for preparing a cooling pipe for a liquid-cooled charging cable according to claim 8, characterized in that, The single-screw extruder is equipped with a melt insulation buffer section at the rear end of the die head, and the cooling adopts a three-stage gradient water cooling: the first stage water temperature is 45-55℃, the second stage water temperature is 30-40℃, and the third stage water temperature is 20-28℃.